Anticipation and preparation for delivery room emergencies. Issue 6 (December 2019) - Chang, Catherine; Perlman, Jeffrey
Abstract: Effective communication is the keystone in the management of delivery room emergencies. A clearly defined framework and "shared mental model" optimize team collaboration and are essential when anticipating and preparing for high-stakes emergent cases. This review defines a framework to build shared mental models using dialogue, pre-briefing, checklists, simulation, debriefing and structured feedback to maintain a cohesive high functioning team. Strategies to approach different emergency lead-times will be discussed, and case examples will be used to illustrate concepts outlined.